Методичний підхід до оцінки економічної активності підприємств у конкурентному середовищі - Полозова, Т. В. (Економіка і право, 2019)
Запропоновано наково-методичний підхід до параметрично-рейтингової оцінки економічної активності підприємств у конкурентному середовищі. Сформовано сукупність оцінних параметрів та часткових показників, що визначають кожнкожний параметр. Рівень економічної активності підприємств визначено показником активності та оберненим до нього показником інертності. Предложен научно-методический подход к параметрическо-рейтинговой оценке экономической активности предприятий в конкурентной среде. Сформирована совокупность оценочных параметров и частных показателей, которые определяют каждый параметр. Уровень экономической активности предприятий определяется показателем активности и обратным ему показателем инертности. This research proposes a methodical approach to parametric-rating estimation of economic activity of an enterprise in a competitive environment. The implementation of the proposed approach involves several steps: determination of the availability of the information-analytical base of the research; formation of a set of estimating parameters (generalized groups), based on available information support; definition of the nomenclature of indicators included in each para metric group; calculation of values of parameters within parameter groups, taking into account the dynamic aspect (parametric estimation); calculation of the general rating of enterprises by adding the places occupied by the enterprise separately for each indicator within each parametric group (rating rating); calculation of the final rating of enterprises, which represents the sum of total ratings for each parameter; estimation of influence of parameters on the final rating of the enterprise; determination of the level of activity of the enterprise in the competitive environment through the calculation of the corresponding indicator of activity; conclusions about the economic activity of enterprises in the competitive environment.In the framework of the proposed approach, a set of valuation parameters from five groups has been formed that cover the identified indicators that influence the level of activity of an enterprise in a competitive environment: availability and use of innovation and investment capital; efficiency of use of production resources; return on equity; financial condition of the enterprise; market positions of the enterprise.The level of activity characterizes the behavior of the enterprise in a competitive environment, is quantified by the change in the overall rating of the enterprise in the dynamics. The reciprocal of the level of activity will characterize the passive behavior of the enterprise in a competitive environment and is determined by the inertia indicator.This approach allows us to determine the company’s final rating, which is subsequently accompanied by a correlation-regression analysis based on the use of the Spirman rank correlation coefficient, as well as the level of activity of the enterprise in a competitive environment.Keywords: the level to activities, competitive environment, indicators of the influence, parameter, rating.
Methodical Approach to Estimation of the Economic Activity Enterprise in Competitive Environment
Методический подход к оценке экономической активности предприятий в конкурентной среде
http://economiclaw.kiev.ua/index.php/economiclaw/article/view/764/723
Keywords: рівень активності; конкурентне середовище; індикатори впливу; рейтинг; уровень активности; конкурентная среда; индикаторы влияния